Integrative analysis of transcriptome and metabolome revealed the mechanisms by which flavonoids and phytohormones regulated the adaptation of alfalfa roots to NaCl stress - Wang, Xiaoshan; Yin, Juncheng; Wang, Jing; Li, Junhao (Frontiers in Plant Science, 2023)
Salinity critically affects the growth and development of alfalfa (Medicago sativa), making it necessary to understand the molecular mechanism of alfalfa's adaptation to salt stress. In this study, alfalfa roots were subjected to salt stress and transcriptomics and metabolomics analyses were performed. The results showed that flavonoid synthesis, hormone synthesis, and transduction pathways may be involved in the alfalfa salt stress adaptation reaction, and that they are related. Combined analysis of differential genes and differential metabolites found that dihydroquercetin and beta-ring hydroxylase (LUT5), ABA responsive element binding factor 2 (ABF2), protein phosphatase PP2C (PP2C) and abscisic acid (ABA) receptor PYL2 (PYL), luteolinidin was significantly correlated with PP2C and phytochrome-interacting factor 4 (PIF4) and (+)-7-isomethyl jasmonate were significantly correlated with flavonol synthase (FLS) gene. (+)-7-isomethyl jasmonate and homoeriodictyol chalcone were significantly correlated with peroxidase (POD). POD was significantly up-regulated under NaCl stress for 6 and 24 h. Moreover, flavonoids, gibberellin (GA), jasmonic acid (JA) and ABA were suggested to play an important role in alfalfa's response to salt stress. Further, GA, ABA, and JA may be involved in the regulation of flavonoids to improve alfalfa's salt tolerance, and JA may be a key signal to promote the synthesis of flavonoids. This study revealed the possible molecular mechanism of alfalfa adaptation to salt stress, and identified a number of salt-tolerance candidate genes from the synthesis and signal transduction pathways of flavonoids and plant hormones, providing new insights into the regulatory network of alfalfa response to salt stress.